Effect of chondroitin sulfate on intraocular pressure in rats - Belforte, Nicolás Adalberto (2010)
PURPOSE: To study the effect of intracameral injections of chondroitin sulfate (CS) on intraocular pressure (IOP), retinal function, and histology in rats. METHODS: Acute or chronic injections of CS were performed unilaterally in the rat anterior chamber, whereas the contralateral eye was injected with vehicle. IOP was daily or weekly assessed by a tonometer. Retinal function was assessed by scotopic electroretinography (ERG) and the visual pathway by flash visual evoked potentials (VEPs), whereas the retinal and optic nerve head structure were examined by histologic analysis. RESULTS: A single injection of 8 mg (but not 2 or 4 mg) CS induced a significant increase of IOP. The increase of IOP induced by a single injection of 8 mg CS lasted for 7 days, whereas chronic (weekly) administration during 10 weeks induced a significant and sustained increase in IOP compared with eyes injected with vehicle. A significant decrease of scotopic ERG a- and b- wave amplitude was observed after 6 and 10 weeks of CS administration. Moreover, a significant decrease in scotopic flash VEP N2-P2 component amplitude was observed in eyes treated with CS for 6 and 10 weeks. A significant loss of ganglion cell layer cells and optic nerve axons was observed in eyes receiving CS for 10 weeks. CONCLUSIONS: These results suggest that exogenous CS simulates the accumulation of CS in primary open-angle glaucoma and that increased amounts of CS could play a key role in the IOP dysregulation characteristic of glaucoma.